2020
DOI: 10.1109/access.2020.3033301
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Active Control With Human Intention Detection of an Upper-Limb Cable-Driven Rehabilitation Robot

Abstract: Rehabilitation robots play an increasingly important role in the recovery of motor function for stroke. To ensure a natural physical human-robot interaction (pHRI) and enhance the active participation of subjects, it is necessary for the robots to understand the human intention and cooperate actively with humanlike characteristics. This study proposed a hybrid active control algorithm with human motion intention detection. The motion intention was defined as the desired position and velocity, which were contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“… represents the Jacobian matrix of CDRR. The details of calculation process are described in equation (Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… represents the Jacobian matrix of CDRR. The details of calculation process are described in equation (Yang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the robot with a compliant control algorithm performs better rehabilitation training for its natural human-robot interaction (HRI) (Niu et al, 2017 ; Yang et al, 2020 ). Since pure force or position control, like that exhibited by the Proportion-Integration-Differentiation (PID) control algorithm (Rosati et al, 2007 ), has proved inadequate for compliant interaction, Hogan ( 1985 ) have proposed an impedance control method which took into account the mechanical interaction between systems and the environment (Veneman et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid active control approach with human intention detection was proposed by Yang et al [94]. To continually analyze the goal location and velocity of the human intention, the human upperlimb model and the minimal jerk model were utilized.…”
Section: Control Laws Used With Motion Intention Estimation In Power ...mentioning
confidence: 99%
“…The impedance control and admittance control algorithms proposed by Hogan et al [21] use the relationship between the force and the position of the robot end to adjust the dynamic impedance characteristics of the system so that the system can express external compliance. Yang et al [22] proposed a hybrid active control algorithm combined with human motion intention and verified the effectiveness of the control algorithm based on the human upper limb model and the minimum continuous motion estimation model. Li et al [23] proposed a variable admittance control method based on human intentions, environmental forces, and environmental stiffness to address physical human-robot interaction (pHRI) coupled to environments of unknown stiffness.…”
Section: Introductionmentioning
confidence: 99%